Effects of artificial desurfacing on alfisols and ultisols in southern Nigeria: II. Changes in soil physical properties - Mbagwu, J.; Lal, R.; Scott, J. (1984)
Changes in soil physical properties of two Alfisols and an Ultisol in southern Nigeria as affected by desurfacing to simulate varying levels of soil erosion were monitored for two consecutive seasons (3 and 7 months after exposure). These investigations were conducted at Ilora (Alfisol), Ikenne (Alfisol), and Onne (Ultisol) in southern Nigeria. All measurements were made on the top 5 cm of the undisturbed control and the desurfaced soils. Following topsoil removal some deleterious changes in soil physical properties occurred on the exposed subsoils. Seven months after removal of 10 cm of topsoil, bulk densities had increased from 1.37 to 1.45 Mg m-3 at Onne, 1.23 to 1.50 Mg m-3 at Ikenne, and 1.27 to 1.42 Mg m-3 at Ilora. These increased bulk densities were reflected in decreased total and macroporosities. Seven months after 10 cm of topsoil removal, total porosity was reduced from 48 to 45% at Onne, 52 to 43% at Ikenne, and 52 to 46% at Ilora. Available water-holding capacities of the surface 5 cm of exposed subsoils following 5 cm of topsoil removal were reduced during 7 months by 61% at Onne, 23% at Ikenne, and 12% at Ilora. Corresponding reductions in saturated hydraulic conductivities of these soils were 75%, 65%, and 35% three months after exposure. Also reduced were the moisture retention at 0.01 MPa suction, and the clay contents of the exposed subsoils. Generally, the magnitude of these changes in physical properties was less for the undisturbed control than for the desurfaced soils. These results strengthen the argument that these structurally unstable soils of the tropics should be managed extremely carefully.